HIV transmission network analysis allows identifying unreported risk factors in HIV‐positive blood donors in France. Issue 4 (16th February 2021) - Cappy, Pierre; Chaillon, Antoine; Pillonel, Josiane; Essat, Asma; Chaix, Marie‐Laure; Meyer, Laurence; Barin, Francis; Tiberghien, Pierre; Laperche, Syria
Abstract: Objectives: As sex between men is a major route of human immunodeficiency virus (HIV) infection in most western countries, restrictive deferral rules for blood donation have largely been implemented regarding men having sex with men (MSM). Here, we sought here to assign unreported HIV risk factors in blood donors (BDs) and reevaluated the MSM‐associated fraction of HIV transfusion residual risk (%RRMSM ). Methods: We applied a genetic distance‐based approach to infer an HIV transmission network for 384 HIV sequences from French BDs and 1337 HIV sequences from individuals with known risk factors (ANRS PRIMO primary HIV infection cohort). We validated the possibility of assigning a risk factor according to clustering using assortative mixing. Finally, we recalculated the %RRMSM . Results: A total of 81 of 284 (28.5%) male and 5 of 100 (5%) female BDs belonged to a cluster; 72 (88.9%) of the 81 male BDs belonged to MSM clusters. After cluster correction, 8 of 67 (11.9%), 4 of 21 (19.0%), and 19 of 88 (21.6%) HIV‐positive (HIV+) male BDs with heterosexual, other, or unknown risk factors could be reclassified as MSM, accounting for 10.9% of the total HIV+ male BDs. Overall, 139 of 284 HIV+ male donors (48.9%) could be considered MSM between 2000 and 2016 in France. Between 2005 and 2016, the %RRMSM increase varied from 0 to 19%, without differing significantly from the %RRMSM before reclassification. Conclusion: Network inference can be used to complement declaration data on risk factors for HIV infection in BDs. This approach, complementary to behavioral studies, is a valuable tool to evaluate the effect of changes in deferral criteria on BD compliance.